Resource Based Learning dalam pembelajaran Bahasa Arab - Nuur, Khaerun Nisa (Diwan: Jurnal Bahasa dan Sastra Arab, 2018)
This article examines a language approach used in teaching Arabic. Studying with Resource Based Learning focusses on students’ point of view, not on the teachers. The students are asked to learn independently, so they experience a change from passive-receptive into active-partisipative strategy. This active-partisipative strategy allows the students in having freedom in learning process. It includes how students prepare their materials by utilizing many kinds of sources. Studying Arabic with Resource Based Learning approach could be applied to improve language skill (maharat al-lughah ), such as listening (maharah al-istima ), speaking (maharah al –kalam ), writing (maharah al-kitabah ), and reading (maharah al-qira’ah ).